Nano-HNS Particles: Mechanochemical Preparation and Properties Investigation. (11th April 2018) - An, Chongwei; Xu, Shuai; Zhang, Yuruo; Ye, Baoyun; Geng, Xiaoheng; Wang, Jingyu
Abstract : Nano-2, 2′, 4, 4′, 6, 6′-hexanitrostilbene (HNS) particles were successfully prepared by a mechanochemical (i.e., high energy milling) process without an organic solvent, which can be viewed as a green technology. The particle size, morphology, specific area, crystal phase, thermal decomposition properties, impact sensitivity, and short duration shock initiation sensitivity were characterized and tested. The diameter of milling HNS is about 89.2 nm with a narrow size distribution and without agglomeration of particles. The formation mechanism of nano-HNS can be viewed as the transformation from thin HNS sheets with a one-dimensional nanostructure to three-dimensional nanoparticles. The nano-HNS particles present a much higherE a and lower impact sensitivity than purified HNS, revealing the outstanding safety properties. From the results of the short duration shock initiation sensitivity, 50% and 100% initiation voltages are decreased compared with those of HNS-IV, indicating the higher initiation sensitivity.